Elemental Contents in Hair of Children from Two Regions in Dar Es Salaam - Najat K. Mohammed (International Journal of Analytical Chemistry)
The work presented in this paper is part of the study which aims at determining the levels of elements in hair of children in Tanzania as a bioindicator of their nutrition and health. In this paper, the levels of trace elements in hair from children living in Dar es Salaam have been analysed. The analysis was carried out by long and short irradiation INAA at the reactor centre of the Institute of Nuclear Physics, Rez Czech Republic. 22 samples were collected from children living at Kiwalani about 12 km from Dar es Salaam city and 16 samples from children living at Mlimani, the main campus of University of Dar es Salaam. A total of 34 elements were found in the hair of the children. There were no big differences between the concentration levels of the essential elements in hair samples collected from the children which might indicate the same food consumption habits.